Co3Mo3N as an alternative for noble-metal catalysts in hydrodeoxygenation of methyl palmitate to diesel range hydrocarbons. Issue 12 (30th May 2022) - Wang, Jiequan; Chen, Xiao; Chen, Xiaozhen; Zhao, Chenxi; Ling, Yu; Liang, Changhai
Abstract : The Co3 Mo3 N catalyst exhibited high efficiency in the hydrodeoxygenation of fatty esters through regulating and optimizing the fine structure and electronic coordination environment. Abstract : Hydrodeoxygenation (HDO) of fatty triglycerides into diesel range hydrocarbons over non-noble-metal catalysts is highly desirable for effectively solving the problems of energy depletion and carbon emission. In this study, the most efficient catalytic system (Co3 Mo3 N) achieves almost complete conversion of methyl palmitate (MPA, a typical ester exchange product of palmitic acid triglyceride and methanol) (99.5%) with 95.0% selectivity to hexadecane under mild conditions, which is attributed to the synergistic interactions between Co and Mo nitrides, forming a unique dual-site configuration of the Co3 Mo3 N catalyst. The reaction kinetics analysis shows that HDO instead of decarboxylation/decarbonylation is the primary reaction route for the hydrogenation of MPA over the Co3 Mo3 N catalyst. Significantly, Co3 Mo3 N exhibits good stability for 72 h. These results suggest that the highly efficient cobalt-molybdenum bimetallic catalyst with an optimized fine structure and electronic coordination environment could achieve the production of clean fuels from the HDO of fatty acids/esters.